Digitization of laboratory equipment using PhET simulation media in applied chemistry practicum - Juwairiah Juwairiah; Meisi Riana; Windiani Windiani (SAINTIS Publishing, 2022)
Understanding the concepts of applied chemistry in the Graphic Engineering Study Program at the Creative Media State Polytechnic is very important to support their field of expertise in understanding more complex material. The Applied Chemistry course consists of various abstract concepts, including acids and bases. The use of computer programs such as PhET media is very important to explain the abstract material. The aim of this study was to describe the use of PhET Simulation, knowing the effectiveness of using PhET Simulation media in acid-base practicum, knowing the advantages and disadvantages of using PhET Simulation in acid-base practicum, and the purpose of this study was to see student learning outcomes after the application of PhET media in learning. The method used is a descriptive method that begins with the manufacture of media devices and student worksheets and performs a descriptive analysis of learning outcomes after the application of learning. The trial subjects in this study were first semester students who programmed the Applied Chemistry course. The research instrument is a learning outcomes test which finds 10 numbers of true and false questions and 5 numbers of essay questions. The results showed that the application of PhET media was effective in acid and base practicum. The average student learning outcomes are 65 ± SD 18 (good category). Based on student assessments after learning, it was found that students were very happy to learn by using PhET media.